FISIOLOGI PERTUMBUHAN, POTENSI AKTIFITAS PRODUKSI N2O DAN GEN FUNGSIONAL PENYANDINYA PADA BEBERAPA ISOLAT BAKTERI DENITRIFIKASI - Agustiyani, Dwi; Laili, Nur; Antonius, Sarjiya (BERITA BIOLOGI, 2018)
Physiological characters of four denitrifying bacteria (Bacillus sp. CPNS, Bacillus thuringiensis UPT1, Brevundimonas diminuta EA1 and Bacillus sp. UPSB) were studied based on the growth ability on various nitrate concentrations and the production of N2O gas. The characters of denitrifying bacteria were also evaluated through the existence of functional genes nirS and nosZ, encoding the nitrite reduction and nitrous oxide reduction enzymes which have important role on denitrification processes. The study showed that Bacillus sp. UPSB and Bacillus sp. CPNS isolates have a linear growth with the increasing concentration of KNO3. The N2O gas production of Bacillus sp. UPSB isolate was relatively high, about 70 ?/l, Bacillus sp. CPNS isolate was 25?/l, while the Bacillus thuringiensis UPT1 isolate was 5 ?/l and Brevundimonas diminuta EA1 isolate was 8 ?/l. It was also indicated that both Bacillus sp. UPSB and Bacillus sp. CPNS had high deninitrification activities. It was confirmed that all isolates were contained functional gen of nirS and nosZ.